Compression behaviour of polypropylene fibre reinforced cellular light weight concrete masonry prism - Vijayalakshmi, Ramalingam; Ramanagopal, Srinivasan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sustainable development of the built environment in developing countries is a major challenge in the 21st century. The use of local materials in the construction of buildings is one of the potential ways to support sustainable development in both urban and rural areas where burnt clay bricks are used predominantly.
Keywords: cellular concrete; lightweight concrete; polypropylene fibre; masonry prism; beton komórkowy; beton komórkowy lekki; włókna polipropylenowe